Factors Associated with Uptake of HIV Testing Services among Men in South Africa - Khoza, Samson S. (University of the Witwatersrand, Johannesburg, 2024)
Background: In 2016, the overall Human immunodeficiency virus (HIV) prevalence rate was estimated at 12,7% and the total number of people living with HIV was estimated at approximately 7,03 million in the South African population in 2016. The World Health Organization recommends that people know their HIV status by getting tested and those who are found to be HIV positive get initiated on treatment early. However, HIV testing rates are below the 90% target and reportedly lower among males in South Africa. Aim: The study aimed to investigate factors associated with HIV Counselling and Testing (HCT) among men aged 18-34 years in South Africa. Methods: The study is a cross-sectional study using secondary data from Testa Boy study conducted by the Centre for Communication Impact in collaboration with Genesis Analytics between April and May 2017. The primary study employed a three multistage sampling approach, where at the first, the country was stratified into nine provinces, with sample size proportional to the population size of each province. After that an initial sub-place (district) was selected randomly from each province. Households were then randomly selected from the enumeration area (EA) or Primary Sampling Unit (PSU) in each sub-place (township/village). Finally, following the household selection, one eligible respondent from each household was selected randomly to participate in the study using a KISH grid that was used to draw a sample of PSUs. Data was collected using a self-administered questionnaire. The primary study constituted of a total of 3,000 male and female participants across all provinces in South Africa. We restricted our study to 1, 388 male participants. The outcome variable of this study was “uptake of HIV Counselling and Testing in the past 12 months”. The data was analysed using Stata SE version 14. Both univariable and multivariable analyses were employed. Results: About 52% of total of 1,388 men had HCT uptake in the past 12 months. Rates of HCT uptake at the provincial level ranged from 41% and 60% with Western Cape recording the high levels and North-west recording the lowest levels. In the multivariable analyses, men residing in provinces outside of the Western Cape demonstrated significantly lower odds of HCT uptake. The odds of HCT uptake was significantly lower among men in the Eastern Cape (AOR0.33, 95%CI 0.33-0.94), Limpopo (AOR0.54, 95%CI 0.30-0.99) and North-west (AOR 0.43, 95%CI 0.22-0.83) compared to the men in Western Cape. Employed men were 1.34 times significantly more likely to receive HCT compared to unemployed men (AOR1.34, 95% CI 1.01-1.77, p=0.039). Middle income (AOR 1.51, 95% CI 1.01-2.27) and low-income men (OR 1.60, 95% CI 1.16-2.21) had significantly increased odds of HCT uptake than rich-income men. With regards to sexual history, men who did not report condom use at first (AOR 0.71, 95% CI 0.53-0.93) and at last sex (AOR 0.68, 95% CI 0.52-0.90) exhibited significantly reduced odds of HCT uptake compared to those who reported condom use. Knowing someone who is HIV positive (AOR 1.40, 95% CI 1.09-1.82) was significantly associated with increased HCT uptake among men. iii Conclusion: The study provides important insights into the patterns and determinants of HCT uptake among men in South Africa. Geographic residence emerged as a key factor, with men from most provinces outside Western Cape exhibiting substantially lower odds of HCT uptake compared to those in Western Cape. Risky sexual behaviours such as not using condoms during sexual intercourse were correlated with low HCT uptake. Targeted interventions, such as expanding community-based HCT initiatives, strengthening health system infrastructure in underserved areas and tailor-made combinations of prevention interventions such as HCT and condom prevention strategies could contribute to increased HCT uptake and better control of the HIV epidemic in the country.
A research report submitted in fulfillment of the requirements for the Master of Public Health, in the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Uptake; HIV Testing Services; men; South Africa; SDG-3: Good health and well-being; SDG-5: Gender equality